Проектирование цифровой платформы для использования креолизованных текстов в обучении русскому языку и литературе (SCIENCE and SOCIETY, 2026)
The article is devoted to the justification of using creolized texts in the digital environment as a necessary tool for adapting education to the visual perception of modern generations of learners.